Extended pneumonectomy for non-small cell lung cancer patients – are the results worth the risk? - Kasprzyk, Mariusz; Dyszkiewicz, Wojciech; Piwkowski, Cezary; Zieliński, Paweł; Brudło, Michalina; Wobszal, Dorota (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction: Extended pneumonectomy is recommended in some patients with locally advanced non-small cell lung cancer (NSCLC) to achieve radical resection of the tumor. Lack of prospective and randomized trials in these patients is one of the reasons why the postoperative risk and the oncological benefits still remain unclear. Aim: The aim of the study was to assess the early and long- term results of extended pneumonectomy in a group of patients with NSCLC. Materials and methods : We analyzed the clinical records of 57 patients (male 49, female 8) operated on between 2000 and 2009. The average age of the patients who underwent the procedure was 58 (between 43 and 75). Extended pneumonectomy including resection of the pericardium was carried out in 16 patients, left atrium in 18 patients, tracheal carina in 15 patients, chest wall in 8 patients, superior vena cava in 4 patients, muscular layer of the esophagus in 2 patients and diaphragm in 2 patients. For statistical analysis Statistica 7.1 software was used. Results : Squamous cell lung cancer was diagnosed in 84.2% of cases. Most of the patients were in stage IIIA (27 patients) or III B (25 patients). Metastases in N2 lymph nodes were found in 54.4% of cases. The overall 30-day mortality was 12.3% and was significantly higher in patients with N2 involvement than in patients with N0/N1 disease (16% vs 8%). The most frequent postoperative complications were supraventricular arrhythmias (21.1%) and broncho-pleural fistula (8.8%). The overall 5-year survival rate was 23%. The multivariate statistical analysis revealed that only one factor, N stage, influenced survival. Conclusions : Extended pneumonectomy is a feasible procedure with an acceptable risk factor in a group of patients with locally advanced NSCLC. Furthermore, using proper selection criteria (exclusion of patients with N2 disease), some patients could reach good local control of the disease or permanent cure.